Microbial responses to warming enhance soil carbon loss following translocation across a tropical forest elevation gradient. (6th September 2019) - Nottingham, Andrew T.; Whitaker, Jeanette; Ostle, Nick J.; Bardgett, Richard D.; McNamara, Niall P.; Fierer, Noah; Salinas, Norma; Ccahuana, Adan J. Q.; Turner, Benjamin L.; Meir, Patrick
Abstract: Tropical soils contain huge carbon stocks, which climate warming is projected to reduce by stimulating organic matter decomposition, creating a positive feedback that will promote further warming. Models predict that the loss of carbon from warming soils will be mediated by microbial physiology, but no empirical data are available on the response of soil carbon and microbial physiology to warming in tropical forests, which dominate the terrestrial carbon cycle. Here we show that warming caused a considerable loss of soil carbon that was enhanced by associated changes in microbial physiology. By translocating soils across a 3000 m elevation gradient in tropical forest, equivalent to a temperature change of ± 15 °C, we found that soil carbon declined over 5 years by 4% in response to each 1 °C increase in temperature. The total loss of carbon was related to its original quantity and lability, and was enhanced by changes in microbial physiology including increased microbial carbon‐use‐efficiency, shifts in community composition towards microbial taxa associated with warmer temperatures, and increased activity of hydrolytic enzymes. These findings suggest that microbial feedbacks will cause considerable loss of carbon from tropical forest soils in response to predicted climatic warming this century.